Impact of coronavirus disease 2019 on the prognosis of mucor mycosis in diabetic patients in Egypt: a comparative multicenter study - Mahmoud ElSamkary; Radwa Elsherif; Tarek M. Saad; Samah M. Fawzy (Journal of the Egyptian Ophthalmological Society)
Aim The current study was designed to figure out the influence of Corona virus infection (COVID-19) on the course and outcome of mucor mycosis in controlled diabetic Egyptian patients. Patients and methods The presented multicenter study compared retrospectively two groups of diabetic patients with clinically and radiologically documented rhino-orbital-cerebral mucor mycosis. The first group included 20 patients who had COVID-19 infection documented clinically, radiologically, and laboratory at the time of admission to the hospital, while the 22 patients in the second group did not. Full ophthalmological evaluation and necessary medications were offered to all patients, and the decision to exenteration was made and performed when appropriate. Medical conditions like diabetes mellitus and other aspects of mucor mycosis were controlled carefully by specialized consultants, and detailed medical reports for morbidity and mortality were provided. Comparisons of the clinical picture, final visual acuity, exenteration, and mortality/survival rates were done between the two groups. Recovered patients were followed up for 4 months after discharge from the hospital. Results COVID-19 infection in the first group aggravated the clinical picture significantly, especially the soft tissue affection like face swelling (P=0.0047) and worsened the final visual outcome (P=0.047). It also increased the rates of ICU admission, exenteration, and death as compared to the non-COVID group by 6, 15, and 11%, respectively (P>0.05). Conclusion Infection by COVID-19 worsened the course and prognosis of rhino-orbital-cerebral mucor mycosis in controlled diabetic patients in the form of a more aggressive clinical picture, exenteration, and death (although statistically insignificant). It also resulted in poorer visual outcome (in acuities CF to 3/60, P=0.047). Early hospitalization, anti-fungal, and surgical exenteration, if needed, increase the survival rate and decrease morbidity.